PERILAKU PEMBELIAN IMPLUSIF DI TIKTOK SHOP PADA MAHASISWA EKONOMI SYARIAH UIN STS JAMBI DALAM PERSPEKTIF EKONOMI SYARIAH - Wahyu Ferdiansyah; Ahsan Putra Hafiz; Agusriandi (Fakultas EKonomi dan Bisnis Islam UIN Sulthan Thaha SAifuddin Jambi, 2026)
This study aims to identify the forms of impulsive buying behavior among students of the Islamic Economics Study Program at UIN Sultan Thaha Saifuddin Jambi on the TikTok Shop platform and to analyze it from an Islamic economic perspective. The research background stems from the increasing prevalence of spontaneous purchasing behavior triggered by digital promotions such as flash sales and free shipping, despite students’ prior understanding of Islamic consumption principles. This research employed a qualitative method with a descriptive approach. The subjects were 32 active students from the 2022 cohort of the Islamic Economics Study Program. Data were collected through in-depth interviews, observations, and documentation, and analyzed using Miles & Huberman’s interactive model, which includes data reduction, data display, and conclusion drawing. The findings reveal that students’ impulsive buying behavior is driven by emotional impulses, ease of transactions, and aggressive promotional strategies on TikTok Shop. The forms of impulsive behavior identified include unplanned purchases, following trends, and buying due to limited-time promotions. Contributing factors include peer influence, visual advertising, large discounts, flash sales, and free shipping offers. From the perspective of Islamic economics, this behavior is considered inconsistent with the principles of tawazun (balance) and the prohibition of israf (extravagance) and tabdzir (wastefulness), as the purchased items often do not meet actual needs or provide minimal benefit.